Keratosis pilaris/Multiple trichoepitheliomas. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2011)
Keratosis pilaris is a disorder inherited as an autosomal dominant trait. It is characterized by hyperkeratosis of the mouths of the follicles, namely the external orifices of the pilosebaceous follicle. Trichoepithelioma is a benign cutaneous tumor with primitive follicular differentiation. It is usually a solitary lesion, but multiple lesions can be present. The latter are inherited by an autosomal dominant trait.